Illocution on Speech Acts of Foreign Students in Indonesian Learning - Latifah Tri Budiasih (Unipdu Jombang, 2019)
AbstractThis research discusses about illocution on speech acts of foreign students in Indonesian Language learning. Illocution is a speech that shows the state of language relating to the situation in general and more free and aims to express something from the speaker to the partner said that the words spoken are the words that really want to be delivered. This research aims to describe the forms of student illocution in Indonesian Language learning. This form of research is qualitative with naturalistic strategy. Data collection techniques in this research using observation techniques, interviews, and document studies. The data in this study are the data in the form of the students illocution acts (assertive, declaration, directives, commissive, and expressive) in learning activities. The data source in this research is the speech acts of a foreign student in Indonesian Language learning. Data illocution in the form is assertive, directives, commissives and expressive.Key words: illocution, foreign student, Indonesian Language.